The Consumer Lending Protection. How to Prevent the Predatory Lending and “Debt Slavery” on the Small-Dollar Lending Market - Mazur, Zofia M. (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis. The present contribution is focused on the lending market, its credit products, and actors, with particular regard to the non-bank small-dollar lenders and the underserved borrowers. The purpose is to analyze some of the specific small-dollar loans and related legislative initiatives from the American and European financial markets which may constitute remedies to the problem of predatory lending. Methodology. The analysis was based on the legal and administrative acts and documents as well as on the doctrine related to the topic examined. Results of the research. The study revealed that the misleading, abusive conducts and numerous sales strategies of professionals operating on the banking market may regard almost any individual. These unethical practices have intensified during the pandemic, becoming particularly dangerous.